Ações realizadas pelos acompanhantes no cenário de parto e nascimento: uma compreensão na fenomenologia social - Gomes, Iris Elizabete Messa (2018)
The process of parturition underwent transformations over the years since when it was carried out at home by traditional midwives until the present day, in which births take place in hospital environment. The process of labor and delivery has the potential to form a bond and transform relationships between people and their families, and the presence of the companion in this process, besides guaranteeing rights, is something that potentiates these transformations. The objective of this investigation was to identify the women companions` actions during the process of parturition and to apprehend their motivations. Qualitative research based on the social phenomenology of Alfred Schutz as a theoretical and methodological framework. The scenario was the Rooming-in Care Unit of a University Hospital, located in the South of Brazil. The participants were 14 companions of women hospitalized in the referred unit and who had accompanied it during the process of labor and delivery. The data production occurred in the period from September 2016 to September 2017, using phenomenological interviews, which stopped when there was sufficiency of meanings. In the analysis, the motivation of the companions was to reassure the choice of the natural birth, to leave the woman calm, to avoid complications and to minimize the pain so that the baby born fast. They have demonstrated a lack of knowledge about the process of successful labor and delivery and their role in this scenario. It is concluded that the companions need clarification regarding their participation in the scenario of labor and delivery.